Diplomasi Kebudayaan Indonesia–Australia Dalam Meningkatkan Sektor Pariwisata Di Bali Pada Tahun 2023 - Erfiana, Ade Irma; Hartati, Anna Yulia (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
Indonesia-Australia bilateral relations have been formally established since December 27 1949. The two countries have increased cooperation in various fields, including tourism. Most Australian tourists holiday in Asia and the Pacific. Their favorite destinations include Bali. The island of Bali has once again been crowned as one of the best tourist destinations in the world by receiving the title of The Best Island in the DestinAsian Readers' Choice Awards. This research has a problem formulation, namely how Indonesian cultural diplomacy to Australia will improve the tourism sector in Bali in 2023. The aim of this research is to find out how Indonesian cultural diplomacy to Australia will improve the tourism sector in Bali in 2023. The theoretical basis used in the research this is cultural diplomacy and tourism. This research uses a qualitative descriptive research method. Data sampling was obtained from previous research and also various articles. Based on the research results, it can be concluded that Cultural diplomacy and Tourism are two concepts that are closely related in the international context. Therefore, Cultural and Tourism diplomacy can be used as an effective diplomatic tool to improve relations between countries and advance national culture. Keywords: Cultural diplomacy, Tourism Sector, Bali